An Analysis of Denotative and Connotative Meanings in College Students’ Interaction - Alfridus Kofi Talan; Adrianus Gude; I Putu Eka Suardana (Focus Journal : Language Review, 2025)
This study, entitled An Analysis of Denotative and Connotative Meanings in College Students’ Interaction, aims to explore how college students use and interpret language in terms of its literal (denotative) and implied (connotative) meanings during their daily communication. Language plays a critical role in interpersonal interaction, and understanding how meaning is constructed and conveyed is essential in a college setting where communication occurs across academic, social, and cultural contexts. The research focuses on identifying the types of words and expressions students commonly use, analyzing how these are understood both literally and contextually, and examining the potential for miscommunication caused by differing interpretations of connotative meanings. The data were collected through observation and documentation of natural conversations among English Department students at Bali Dwipa University, followed by a semantic analysis based on theories of meaning. The findings reveal that while students are generally aware of denotative meanings, they frequently rely on connotative meanings to express emotions, attitudes, or social alignment. However, varied personal and cultural backgrounds sometimes lead to misinterpretation, particularly with words or phrases that carry strong emotional or cultural connotations. The study concludes that there are 20 utterances highlighting the rich interplay between denotative and connotative meanings in everyday student communication. While the denotative meanings provide a straightforward, literal understanding of the expressions, it is the connotative meanings that reveal deeper social, emotional, and relational nuances. An increased awareness of both denotative and connotative meanings can improve communication effectiveness and reduce misunderstandings in academic and informal settings.